Luther Then and Now - Hampson, Margaret Daphne (Toronto journal of theology, 2017)
As we approach the Reformation half-millennium we should recognize how much we owe to Luther, but also ponder what a different world is ours. We owe to the Reformation that the hegemony of the medieval world was overcome, leading to modern liberties and individualism; the impetus given to the vernacular; and the overcoming of Aristotelianism. Theologically, Luther has an "exploded" notion of the self as the Christian lives extrinsically, and a non-local notion of the post-Ascension Christ, possibly also of God. He has great insight psychologically. However, tectonic plates have shifted. Epistemologically, it was grasped in the Enlightenment that nature and history form an interrelated causal nexus, disallowing a particularity such as Christians claim took place in history. Ethically, there is a problem for us around both hierarchy and heteronomy, such that it is difficult to know how our values could be reconciled with a religion of revelation. That Luther could scarcely have recognized the equality of women is beside the point; the Christian religion, which he espoused, has fed gender hierarchy. Lutheranism has a peculiar difficulty in that the self must once and again be broken, that the person may live extrinsically in Christ in God; whereas women, in particular, value a once-born sense of self and growth from within. The changes, subtle and complex, can in no way be revoked. We, in our time also, should not lack courage in finding new ways to conceptualize that which is God commensurate with both our epistemology and our ethics.